مغلطائی کی الإعلام اور سیوطیؒ کی مصباح الزجاجۃ : اسالیب ومناہج کا تقابل: A COMPARATIVE STUDY OF MEHODOLOGIES AND STYLES OFMUGHALTAI’S AL-ILAM AND SUYUTI’S MISBAH AL-ZUJAJAH (Zia e Tahqeeq, 2025)
Imam Ala al-Din Mughaltai was a renowned Hanafi scholar of Egyptwho had a great impact on his subsequent Muslim thought. He was anAsh’ari theologian and produced numerous books in the field ofIslamic Studies. His writings had always been in a wide circulation.His Al-Ilaam bil-Sunnah is comentry on Ibn-e-Majah’s Sunan. Thiscommentary is known as Sharh Mughaltai. Imam Jalal al-Din Suyutiwas another prominent Muslim Scholar of Egypt who had a greatcontribution in Islamic literature. He wrote numerous books in almostall fields of Islamic Studies i.e. Quranic sciences, Hadith and Fiqh,Theology and Sufism. Misbah al-Zujajah is one of his major books inHadith. It is a commentary on Al-Sunan by Ibn Maja. This paper aimsto compare both commentaries of Mughaltai and Suyuti. This studyhelps to understand the methodologies and styles of writing of bothEgyptian scholars.